Psychology, Development and Social Policy in India - Tripathi, R. C.; Sinha, Yoganand; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2014)
This book examines how and where psychology can engage itself in the framing of social policies for national as well as human development in India. Although the role that psychological knowledge can play in informing social policy decisions has been discussed for a long time, psychologists by and large have had little role in framing policy decisions related to such important domains as education, health, social justice and social inclusion. Policy makers, not only in India, but more or less everywhere have focused on interventions at the macro level, which has led them to ignore the root causes of the problems lying at the micro level. However, with the more humanistic approaches now being followed by economists and other social scientists, the person in society is slowly taking centrestage. Micro-level variables like happiness, the wellbeing of individuals and the social relationships within which people define themselves are becoming important. Therefore, this book discusses important psychological issues related to human development; particularly, health and education, social justice, social integration, environment and work organizations, besides focusing on some general issues relating to the logic of making social policies. It is a first-ever attempt in India to inform policy makers about how micro-variables can be a crucial factor to consider while framing social policies.
Chapter 1: Introduction: The Psychological Coordinates of Social Policy in India -- Chapter 2: Social Research and Public Policy -- Chapter 3: Psychology and National Development -- Chapter 4: Human Development: Concept and Strategy -- Chapter 5: Education: Path to Development and Happiness in Rural India? -- Chapter 6: Language Policy and Education: Towards Multilingual Education -- Chapter 7: Learning Disability: Issues and Concerns with Implications for Social Policy -- Chapter 8: Social Policy and Mental Health: The Case of India -- Chapter 9: Psychology and Physical Disability Policies -- Chapter 10: Relevance of Traditional Healing and Health Care Practices in India -- Chapter 11: Psychological Impact of Poverty and Socio-Cultural Disadvantage: Some Problems of Policy and Intervention Research -- Chapter 12: Research on Distributive Justice: Implications for Social Policy -- Chapter 13: The Hindu-Muslim Divide: Building Sustainable Bridges -- Chapter 14: Gender Role Transformation and its Implication for Culture and Policy -- Chapter 15: The Environment-Behaviour link: Challenges for Policy Makers.
Keywords: Philosophy (General).; Social policy; Psychology -- History; Psychology; General Psychology; Social Policy; History of Psychology